Strategi Pendistribusian Buah Lokal di Kota Semarang - Ratnawati, Andalan Tri; Hikmah (Universitas Brawijaya, Indonesia, 2015)
Market opportunities for local fruits are still very widely as the growth of publicawareness on fruits consumption. According to the poll Compass (October 16, 2011), thecommunity is still fond of local fruit, from the 446 respondents, 74.9% of respondents preferconsuming local fruit to the fruit imports. Fruits shipped from farmers to retailers, estimatedreach 30% damaged before it reaches to the consumer. This is in contrast to the fruits importedby traveling are still in a good condition. This study aims to make local fruits distributionstrategy at Semarang. The population in this study are farmers, retailers, wholesalers,middlemen. The research methods use quantitative and qualitative descriptive analysis.The pattern of fruits local distribution at Semarang is most farmers sell to middlemen, proceedto wholesalers, retail traders, and then forwarded to the consumer. Model local fruitsdistribution strategy in this study is the farmers forwarded to farmers'coordinator, continuedto the outlets, then forwarded to consumer, or from the farmers'coordinator, continuedto outlets, then forwarded to the consumers.